HUBUNGAN ANEMIA PADA KEHAMILAN DENGAN KEJADIAN BERAT BADAN LAHIR RENDAH - Indah R. Mendrofa, Titian; Samuel P. Hutasoit, Eka; Syahrir, Lesmana (Jurnal Kedokteran Methodist, 2020)
Background : Anemia in pregnancy is defined as a pregnant woman’s hemoglobin level <11g /dL. Anemia is a decrease in red blood cells (erythrocytes) or hemoglobin mass in the blood circulation so that it is unable to fulfill its function as an oxygen carrier to all tissues. Anemia in pregnancy can be a risk factor for low birth weight (LBW). LBW is a baby born weighing less than 2500 grams. LBW can increase perinatal and neonatal mortality which affects developmental disorders and decreasing of intellectual function. Methods : This study uses a study literature review. Results: The literature review, there were 21 scientific articles / journals related to the inclusion criteria with secondary data. There were 15 articles that stated there was a relationship between anemia in pregnancy and the incidence of low birth weight, while 6 articles stated that there was no relationship between anemia in pregnancy and the incidence of low birth weight. Conclusion : There is a correlation between anemia in pregnancy and the incidence of low birth weight.